PE#02 Price escalation for internal plumbing & sanitary works rev.03 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the resubmission of revised price for internal plumbing & sanitary works of BRACU new campus project.